Study Of Syntactic Features And Meaning Of The Limitative Expression “saja” In Indonesian, And The Application In Japanese Translation - Utari Novella (IZUMI, 2020)
Indonesian is the word order of SVO. The limitative expression in Indonesian generally functions as an adverb in the sentence. Adverbs to express limitative expression in Indonesian are classified in some variations. In this paper, the researcher clarified the structure and meaning of limitative expression saja in Indonesian. Referring to the term used by Alwi (1998), Sneddon (2000) and Chaer (2009), saja appears to the right of nouns and verbs. Sneddon (2006) uses the word ‘limiter’ to show the meaning of saja. The research methodology used descriptive using actual data. Data analysis was conducted using theory, as stated by Alwi (1998), Sneddon (2000, 2006), and Chaer (2009). When translated into Japanese, the meaning of saja can be converted into various particles. The definition of each of the particles that express the limitation is considered based on the theory of Sawada (2007), Numata (2009), and Nitta (2009). The results of the research are, saja can be classified into five categories; there are uniqueness, multiplicity, continuity, the minimum limit, and extremity. In Japanese, each meaning can be translated into toritatejoshi dake, bakari, and sae.